Algorithm of Decision Making Process by Corporate Management and Ways of Resolving Crisis Situations Caused by Accounting, Financial and Economic Risks - Svoboda, Emil; Bittner, Libor; Svoboda, Patrik (Communications - Scientific letters of the University of Zilina, 2002)
The scientific paper presents an algorithm and methods of strategic decision making process by top management and ways of eliminating and resolving crisis situations caused by accounting, financial and economic risks. The algorithm deals with a business’s lifetime stages and presents the risks, as well as the methods to analyse such risks, based on both external and internal factors of managerial environment. The aim is to define the risks and ways of eliminating them. The paper includes results of the EP 7260 (Brno, 1998–2000), GA MSM 431100007 (Brno 2000–2001)s and EP – 12/2001–2003 (Brno, 2001–2002) research projects. Methodology is based on analytical-synthetic methods, comparison, controlled interview, strategic decision making process, crisis management methods and selected methods of the accounting, financial and economic analysis. The paper also follows up the works published at conferences and in scientific journals FŠI ŽU Žilina (2000), SPU FEM Nitra (2000–2002), PEF ČZU Praha (2000–2001) and IAES (Vienna, 1999), (Montreal, 1999), South Carolina (2000), and Paris (2002). Results of the research have been verified on selected enterprises in the process of dealing with crisis situations which afflicted these enterprises owing to unsuitable reactions to changes in the managerial environment.